Designing the Quality Assurance Agency E-Document Application at the National University Website Based: Designing the Quality Assurance Agency E-Document Application at the National University Website Based - Dianita Ayu Putri Astari; M. Iwan Wahyuddin; Deny Hidayatullah (Institute of Computer Science (IOCS), 2020)
The National University Quality Assurance Agency is an agency that has the function of maintaining and improving quality so that quality is always guaranteed as well as possible. One of its duties is collecting documents for lecturers and employees. Documents are accurate evidence of recording information sources used for selecting, processing or storing information. This document is very important for seeing the level of achievement of organized activities. The purpose of this E-Document Application was made to optimize the creation of an electronic document processing system for the Quality Assurance Agency (BPM) at the National University in collecting the documents needed so that the documents are stored properly, facilitating the search process and maintaining because often this document processing is still carried out Manually, difficulty in searching and disorganized in their storage. The design of this application uses software, namely the programming language used is PHP, bootstrap, XAMPP, MySQL, using the Unified Modeling Language (UML) method and testing using black box testing. The result of designing this application is a Website-based E-Document information system and is expected to help the work unit to find documents quickly and does not take a long time in searching and stored regularly. using the Unified Modeling Language (UML) method and testing using black box testing. The result of designing this application is a Website-based E-Document information system and it is hoped that it can help the work unit to find documents quickly and does not take a long time in searching and stored regularly. using the Unified Modeling Language (UML) method and testing using black box testing. The result of designing this application is a Website-based E-Document information system and is expected to help the work unit to find documents quickly and does not take a long time in searching and stored regularly.